Clinical Trial Combining Botulinum Toxin A Injection and Fissurectomy for Chronic Anal Fissure: A Dose-Dependent Study - Nuha Alsaleh; Abdullah I. Aljunaydil; Gaida A. Aljamili (Journal of Coloproctology, 2022)
Background Anal fissure is a common surgical disease that is usually treated conservatively. The golden surgical treatment for anal fissure is lateral internal sphincterotomy, but it may result in multiple complications. Therefore, other treatment methods have recently been introduced, and one of them is the injection of botulinum toxin A (BTA) and fissurectomy. In the present study, we aim to evaluate the effectiveness of the combination of fissurectomy and BTA injection in the treatment of chronic anal fissure by single surgeon. Materials and Methods The present is a non-randomized prospective cohort study conducted by a single surgeon in Saudi Arabia. Our sample was composed of 116 female patients, with mean age of 36.57 ±  11.52 years, who presented to our Surgical Outpatient Clinic with chronic anal fissure between October 2015 and July 2020, and were treated with BTA injection combined with fissurectomy. They were followed up for 1, 2, 3, 4, and 8 weeks, and after one year to evaluate the efficacy and safety of the treatment. The main outcomes analyzed were symptomatic relief, complications, recurrence, and the need for further surgical intervention. Results The treatment with BTA injection combined with fissurectomy was effective and safe in 115 patients (99.1%) at 1 year of follow-up. A total of 5 patients experienced recurrence at 8 weeks, which resolved completely with pharmacological sphincterotomy, and 12 patients experienced minor incontinence, which disappeared later. Conclusion In total, 70 units of BTA injection combined with fissurectomy is a suitable second-line treatment of choice for chronic anal fissure, with a high degree of success and a low rate of major morbidity.